2022
DOI: 10.1002/ece3.9032
|View full text |Cite
|
Sign up to set email alerts
|

Temporal activity patterns of North China leopards and their prey in response to moonlight and habitat factors

Abstract: The nocturnal activities of predators and prey are influenced by several factors, including physiological adaptations, habitat quality and, we suspect, corresponds to changes in brightness of moonlight according to moon phase. In this study, we used a dataset from 102 camera traps to explore which factors are related to the activity pattern of North China leopards ( Panthera pardus japonensis ) in Shanxi Tieqiaoshan Provincial Nature Reserve (TPNR), China. We found that nocturnal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 87 publications
(160 reference statements)
1
13
0
Order By: Relevance
“… Jiang et al, 2015 ; Allen et al, 2020 ; Searle et al, 2020 ; Snider et al, 2021 ; Loveridge et al, 2022 ), and predator-prey overlap ( e.g . Dias, de Campos & Rodrigues, 2018 ; Havmøller et al, 2020 ; Palei et al, 2022 ; Sehgal et al, 2022 ; Zaman et al, 2022 ), have been performed worldwide. However, until relatively recently, few studies have investigated African leopard ( P. p. pardus ) ecology in human-disturbed landscapes (see Marker & Dickman, 2005 ; Williams et al, 2017 ; Strampelli et al, 2018 )—particularly in commercial agricultural regions.…”
Section: Introductionmentioning
confidence: 99%
“… Jiang et al, 2015 ; Allen et al, 2020 ; Searle et al, 2020 ; Snider et al, 2021 ; Loveridge et al, 2022 ), and predator-prey overlap ( e.g . Dias, de Campos & Rodrigues, 2018 ; Havmøller et al, 2020 ; Palei et al, 2022 ; Sehgal et al, 2022 ; Zaman et al, 2022 ), have been performed worldwide. However, until relatively recently, few studies have investigated African leopard ( P. p. pardus ) ecology in human-disturbed landscapes (see Marker & Dickman, 2005 ; Williams et al, 2017 ; Strampelli et al, 2018 )—particularly in commercial agricultural regions.…”
Section: Introductionmentioning
confidence: 99%
“…This may have biased their results, but the nature of these effects is unknown. Studies contrasting prey and predator activity (e.g., Foster et al, 2013 ; Tambling et al, 2015 ; Smith et al, 2020 ; Zaman et al, 2022 ) that apply time‐to‐independence filters may need to be revisited. This is due to the demonstrated differences in the effects of time to independence between these two guilds.…”
Section: Discussionmentioning
confidence: 99%
“…The daily activity patterns of an animal reflect its phylogeny and the risks and rewards of activity or inactivity that determine fitness (Halle, 2000; Roll et al, 2006). Measuring and comparing activity patterns provides key insights into the behavioral trade‐offs that result in activity, such as food availability, mating opportunities, physiological processes, predation risk, and environmental constraints (Owen‐Smith, 1998; Tambling et al, 2015; Weyer et al, 2020; Zaman et al, 2022). These insights, together with the emerging availability of abundant activity data from camera traps, have led to renewed interest in describing the free‐ranging activity patterns of species and populations and comparing these between groups (e.g., predators and their prey, those at risk of predation vs. those not, and between time periods—Delisle et al, 2021; Diete et al, 2017; O'Connell et al, 2011; Rowcliffe et al, 2014; Smith et al, 2020; Zaman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite intuitive expectations for attraction to the moonlight (lunar philia) or avoidance of moonlight (lunar phobia) and accumulating evidence for each, our knowledge of wildlife responses to the moon and their prevalence in nature is still disjoint. While some species seem to respond strongly to lunar illumination (Kronfeld-Schor et al 2013), others apparently do not respond at all (de Matos Dias et al 2018, Zaman et al 2022), for reasons not fully understood. The most comprehensive assessment of species responses to moonlight is a meta-analysis of 58 species that found that moonlight reduced the activity of species in open habitats yet increased the activity of species in forested environments (Prugh and Golden 2014).…”
Section: Introductionmentioning
confidence: 99%